Classification Of Diseases In Patients Based On Factors Environment Using The K-Means Algorithm At Puskesmas Subdistrict Selesai - Ramadhani, Sisca; Sihombing, Marto; Simanjuntak, Magdalena (Yayasan Kita Menulis, 2023)
Diseases caused by the environment are disease phenomena caused by the relationship between humans and environmental factors. Diseases that occur due to the environment that must be known by the public are such as ISPA, dermatitis, diarrhea, pulmonary TB, and so on. In the area of the Kecamatan Selesai, there are still many environmental conditions Not yet such as damaged roads and smoke from factories that cause air pollution, so with condition environment like This can affect public health. Puskesmas Selesai is Public health center Which located in region Kecamatan Selesai. The data of patients seeking treatment at this puskesmas are only used archives and to view the patient's medical history. The public should know about symptoms of the disease in order to get appropriate services. In data mining techniques for clustering patient disease data can be used as new information useful for puskesmas or related as material counseling to society. The purpose of this study is to analyze the results of the application of data mining using K-Means Clustering in grouping patient diseases based on the environment with age, village and disease diagnoses variables.